Randomized, Double-Blind, and Placebo-Controlled Trial of Clenbuterol in Denervated Muscle Atrophy. (15th August 2011) - Jiang, Guang-Liang; Gu, Yu-Dong; Zhang, Li-Yin; Shen, Li-Ying; Yu, Cong; Xu, Jian-Guang
Abstract : Objectives .β 2 -adrenergic agonists, such as clenbuterol, have been shown to promote the hypertrophy of healthy skeletal muscles and to ameliorate muscle wasting in a few pathological conditions in both animals and humans. We intended to investigate the clinical efficacy of clenbuterol on attenuating denervation-induced muscle atrophy. Methods . A double-blind, placebo-controlled, parallel, and randomized trial was employed. 71 patients, suffering from brachial plexus injuries, were given either clenbuterol (60 μ g, bid) or placebo for 3 months. Before and at the end of the study, patients were given physical examinations, biopsies of biceps brachii, electromyograms (EMGs), and other laboratory tests. Results . Compared with placebo treatment, clenbuterol significantly mitigated the decreases in cross-sectional areas of type I and II muscle fibers and alleviated the reduction in fibrillation potential amplitudes, without any adverse effects. Conclusions . Clenbuterol safely ameliorated denervated muscle atrophy in this cohort; thus larger clinical studies are encouraged for this or otherβ 2 agonists on denervation-induced muscle atrophy.